2019
DOI: 10.3390/molecules24030606
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-Mass Spectrometry (GC-MS) Analysis of Essential Oils from AgNPs and AuNPs Elicited Lavandula angustifolia In Vitro Cultures

Abstract: The aim of this study was to determine how the addition of gold and silver nanoparticles to culture media affects the composition of essential oils extracted from Lavandula angustifolia propagated on MS media with the addition of 10 and 50 mg·dm−3 of gold (24.2 ± 2.4 nm) and silver (27.5 ± 4.8 nm) nanocolloids. The oil extracted from the lavender tissues propagated on the medium with 10 mg·dm−3 AgNPs (silver nanoparticles) differed the most with respect to the control; oil-10 compounds were not found at all, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…This was also dissimilar to a sample from lavender essential oil obtained from the inflorescences of L. angustifolia “Sevtopolis” cultivated in western Romania, which had linalyl acetate (40.7%), linalool (22.5%), caryophyllene (8.9%), and lavandulyl acetate (7.5%) as its principal components [51]. In addition, it has been recently observed that the chemical composition of L. angustifolia essential oil can be modified by the application of gold and silver metals as elicitors, decreasing lower-molecular-weight compounds such as α- and β-pinene, camphene, δ-3-carene, p -cymene, 1,8-cineole, pinocarveol, etc., which are replaced by higher-molecular-weight compounds such as α-cadinol 9-cedranone, cadalene, α-bisabolol, and (E,E)-farnesol, varying the biological properties [52]. Other presentations, such as hydrolates, produced a reduction in volatile compound content and a reduction in antioxidant activity [53].…”
Section: Resultsmentioning
confidence: 99%
“…This was also dissimilar to a sample from lavender essential oil obtained from the inflorescences of L. angustifolia “Sevtopolis” cultivated in western Romania, which had linalyl acetate (40.7%), linalool (22.5%), caryophyllene (8.9%), and lavandulyl acetate (7.5%) as its principal components [51]. In addition, it has been recently observed that the chemical composition of L. angustifolia essential oil can be modified by the application of gold and silver metals as elicitors, decreasing lower-molecular-weight compounds such as α- and β-pinene, camphene, δ-3-carene, p -cymene, 1,8-cineole, pinocarveol, etc., which are replaced by higher-molecular-weight compounds such as α-cadinol 9-cedranone, cadalene, α-bisabolol, and (E,E)-farnesol, varying the biological properties [52]. Other presentations, such as hydrolates, produced a reduction in volatile compound content and a reduction in antioxidant activity [53].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies confirmed the suitability of silver NPs (AgNPs) as elicitors in plant tissue cultures Somayeh 2013, 2014). The micropropagation of lavender on media supplemented with AgNPs and gold nanoparticles (AuNPs) resulted in significant changes in the composition of essential oils isolated from its tissues (Wesołowska et al 2019). This may indicate the possibility of using these molecules as elicitors.…”
mentioning
confidence: 99%
“…Gas chromatography-mass spectrometry (GC-MS) was used to identify compounds in essential oils and extracts of n-Hex and its VLC fraction of n-Hex extract. GC-MS analysis was performed on a Shimadzu GC-MS QP 5050A gas chromatograph-mass spectrometer tted with a fused capillary column DB-1 (60 m, 0.25 mm id, lm thickness 0.25 µm) [30]. Helium was utilized as the carrier gas, at a ow rate of 1 ml/min.…”
Section: Identi Cation Of Volatile Compounds In Non-polar Samplesmentioning
confidence: 99%